H2 Fuels from Photocatalytic Splitting of Seawater Affected by Nano-TiO2 Promoted with CuO and NiO - A.-J. Simamora; Fang-Chih Chang; H. Paul Wang; T.-C. Yang; Y.-L. Wei; W.-K. Lin (International Journal of Photoenergy)
To enhance H2 yields from the photocatalytic splitting of seawater, better photocatalysts such as nanostructured TiO2 promoted with NiO (2.5%) and CuO (2.5%) have been studied in the present work. The accumulated H2 yielded from the photocatalytic splitting of seawater containing oxalic acid (50 mM) as the sacrificial reagents on CuO/nano-TiO2 is 8.53 μmol/gcat after the 5 h radiation. On the NiO/nano-TiO2 photocatalyst, the H2 yield is relatively low (i.e., 1.46 μmol/gcat). Note that the hole scavenging with chlorides in seawater may be associated with the less H2 yielded from the seawater photocatalysis (on CuO/nano-TiO2) if compared with that from water (42.4 μmol/gcat).